Knowledge use in the development of sugar-sweetened beverage tax policy in Mexico and Chile: a qualitative analysis - Gordon C Shen, PhD; Benjamin McCarthy, BA; Melissa Fuster, PhD; Sarah Lewis, PhD; Sahai Burrowes, PhD (Elsevier, 2020)
Background: Knowledge use is an integral theme of public policy studies. National obesity policy merits attention given its technical and social complexity. Scientific evidence about the obesity epidemic has been contested and obesity prevention is political in nature because it raises tensions between population health promotion and the principle of non-interference in citizens' lives. Countries that are early adopters of obesity policy are enmeshed in this two-fold complexity. In this study, we examine the knowledge that was used in the development of sugar-sweetened beverage (SSB) tax policy in Mexico and Chile. Methods: We conducted semi-structured interviews with key informants from the epistemic community, civil society, and food and beverage industry. We also collected documents about SSB tax policy in Mexico, Chile, and elsewhere in Latin America. Interviews were professionally transcribed and translated verbatim. We analysed the transcripts and published material using the same coding scheme. We also conducted a bibliometric analysis of the documents collected. Findings: Between February and August, 2018, we interviewed 24 key informants: 16 researchers, five civil society representatives, and three food and beverage industry representatives; nine from Mexico, seven from Chile, and eight international respondents. We included 215 total documents dated from Jan 17, 2002, to Feb 11, 2020, including 175 journal articles, 25 newspaper articles, eight books, five conference papers, one report, and one master's thesis. Three themes emerged from our dataset. First, interviewees focused on the evidence that showed an immediate relation between tax and reduced consumption of SSB rather than SSB's long-term impact on population health. Second, interviewees endorsed the concept of "policy-based evidence making", defined as an increase in the production of scientific evidence after SSB tax policy was enacted in the two countries. Lastly, the document analysis showed that each type of respondent cited literature published by their peers. Interpretation: The study of public policy should include the evaluation of evidence in the national response to population health problems. Our findings on causality, knowledge gaps, and citation homophily have implications for the adoption of controversial health policy. Funding: PSC-CUNY Award (#60806-00), jointly funded by The Professional Staff Congress and The City University of New York.